EDUCATIONAL PROBLEMS IN THE CONTEXT OF SOCIAL PSYCHOLOGY - Sanjar KASIMOV, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
Today, raising young people with high knowledge and potential is one of the urgent issues. There is a growing need to study the existing problems in the education system, namely, from a social psychological perspective. This article covers issues such as socio-psychological problems, the study of the problems of the current education system, the factors of their emergence, prevention and their solution. Also, the aspects of the relationship between the issues raised and a number of psychological approaches are highlighted.